Somatosensory evoked potentials in clinical practice: a review - Otto Jesus Hernández Fustes; Cláudia Suemi Kamoi Kay; Paulo José Lorenzoni; Renata Dal-Prá Ducci; Lineu Cesar Werneck; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
Abstract The authors present a review of the current use of somatosensory evoked potentials (SSEPs) in neurological practice as a non-invasive neurophysiological technique. For this purpose we have reviewed articles published in English or Portuguese in the PubMed and LILACS databases. In this review, we address the role of SSEPs in neurological diseases that affect the central nervous system and the peripheral nervous system, especially in demyelinating diseases, for monitoring coma, trauma and the functioning of sensory pathways during surgical procedures. The latter, along with new areas of research, has become one of the most important applications of SSEPs.